One-Pot Synthesis of Epirubicin-Capped Silver Nanoparticles and Their Anticancer Activity against Hep G2 Cells - Jun Ding; Guilin Chen; Guofang Chen; Mingquan Guo (Pharmaceutics, 2019)
Epirubicin-capped silver nanoparticles (NPs) were synthesized through a one-pot method by using epirubicin as both the functional drug and the reducing agent of Ag+ to Ag0. The preparation process was accomplished in 1 h. In addition, the obtained epirubicin-capped silver nanoparticle was characterized by transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDX), and infrared spectroscopy. The results showed that a layer of polymer epirubicin had formed around the silver nanoparticle, which was 30-40 nm in diameter. We further investigated the antitumor activity of the prepared epirubicin-capped silver nanoparticle, and the half maximal inhibitory concentration (IC50) against Hep G2 cells was 1.92 μg/mL, indicating a good antitumor property of the nanoparticle at low dosage.